Fairness views and political preferences: Evidence from a large online experiment - Daniel Muller; Sander Renes (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
We elicit distributional fairness ideals of impartial spectators using an incentivized economic experiment in a large and heterogeneous sample of the German population. Our dataset allows us to relate our experimental data on fairness ideals to a large range of socio-demographic characteristics, political preferences and revealed charitable behavior. We document several empirical facts: i) egalitarians are the predominant type, even though egalitarian allocations are Pareto-dominated by maxi-min allocations; ii) females are more egalitarian than men; iii) men are relatively more efficiency-minded; iv) maxi-max preferences are empirically irrelevant; v) left-leaning voters are more likely to be egalitarians whereas right-leaning voters are more likely to be efficiency-minded; and vi) young and highly-educated participants hold di.erent fairness ideals than the rest of the population. Moreover, we show that the experimentally elicited fairness types predict preferences for redistribution and social spending. We also find that egalitarians are more likely to donate to charity than efficiency-minded people, even after controlling for a range of covariates. Hence, our paper also contributes to the emerging literature examing the external validity of laboratory experiments on fairness preferences.
Keywords: C90; D31; D63; 330; Distributional fairness; impartial spectator; representative online experiment; external validity; political attitudes